2021
DOI: 10.48550/arxiv.2104.12234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arcsine Law and Multistable Brownian Dynamics in a Tilted Periodic Potential

J. Spiechowicz,
J. Łuczka

Abstract: Multistability is one of the most important phenomena in dynamical systems, e.g. bistability enables the implementation of logic gates and therefore computation. Recently multistability has attracted a greatly renewed interest related to memristors and graphene structures. We investigate tristability in velocity dynamics of a Brownian particle subjected to a tilted periodic potential. It is demonstrated that the origin of this effect is attributed to extreme value statistics in the form of arcsine law for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Finally, in Ref. [52] it is shown that the real-time velocity dynamics in this system is not bistable but rather multistable.…”
Section: A Diffusion Quantifiersmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, in Ref. [52] it is shown that the real-time velocity dynamics in this system is not bistable but rather multistable.…”
Section: A Diffusion Quantifiersmentioning
confidence: 93%
“…Consequently, x(t) ∼ v t, the leading term in the mean square displacement is ∆x 2 (t) ∼ t 2 and one observes the persistent ballistic diffusion with D(t) → ∞. Its constancy is guaranteed via the strong ergodicity breaking [52,55], i.e. there are two mutually inaccessible attractors for the average velocity of the particle in the phase space of the system.…”
Section: Residence Probabilitiesmentioning
confidence: 97%